IMPROVING THE RECONSTRUCTION OF DENTAL OCCLUSION USING IMPLANTS IN ELDERLY PATIENTS - Mihaela Mitrea; Razvan Radu Maxim; Allia Dmour; Marius Constantin Moraru; Edlibi Al Hage Walid; Razvan Tudor Tepordei; Ovidiu Mihail Stefanescu; Angela Tecuceanu; Oana Elena Ciurcanu; Irina Luciana Gurzu; Catalin Mihai Buzduga; Simona Niculescu; et al. (Romanian Society of Oral Rehabilitation, 2022)
Immediate function has become an accepted treatment modality for fixed restorations in completely edentulous jaws. Guided implant surgery is considered as a safe and minimally invasive flapless procedures. A total of 26 patients (10 males and 16 females, mean age 50.0+/- 15.5 years) were enrolled in the present retrospective clinical study, 265 implants post-extractive were installed, immediately loaded by means of a provisional fixed full arch. In our present study, a total of 265 SKY classic fast @ fix implants from Bredent were used for the reconstruction in 3 cases of both jaws, for the reconstruction of a single jaw in 5 cases, for the reconstruction of the maxilla in 6 cases and for the reconstruction of the mandible in 5 cases. Within the limits of this study, complete-arch fixed reconstruction by means of guided surgery and immediate loading of implant placed in fresh extraction sockets appears to be a reliable and successful procedure. Further long-term prospective studies on a larger sample of patients are needed to confirm these positive outcomes.